Basis Epistemologi Tafsir Nashr Hamid Abu Zayd dalam Kitab Mafhum an-Nas dan Implikasinya Terhadap Desakralisasi Quran - Saprudin, Aris (INDO PUBLISHING, 2025)
Nasr Hamid Abu Zayd's thinking on the Qur'an as a muntaj tsaqafi (cultural product) and nash insani (human text) has sparked widespread debate in contemporary Islamic studies. This study aims to uncover the epistemological basis of Abu Zayd's ideas in his major work, Mafhum an-Nas, and analyze its implications for the concept of the sacrality of the Qur'an. Using a qualitative literature study method, this study traces the roots of Abu Zayd's thinking through an analysis of his biography, educational background, and the socio-historical context of Egypt surrounding him. The results show that Abu Zayd's epistemology is formed from a synthesis of Mu'tazilite rationalism, particularly the doctrine of the Qur'anic khalq; the linguistic-literary approach of the Amin al-Khuli school; and a modern hermeneutical framework. This foundation leads him to the conclusion that the Qur'an, as a text embodied in human language and history, is necessarily a human text open to critical analysis. The main implication is the desacralization of textual interpretation by strictly distinguishing between historical meaning (al-ma'nā) and contemporary significance (al-maghzā). This study demonstrates how Abu Zayd's method radically shifted the approach to revelation from theological-dogmatic to linguistic-historical, with the aim of liberating the text from ideological hegemony and making it relevant to the challenges of the times.